EFFECT OF ADDITION OF SACCHAROSE TO THE SENSORY PROPERTIES OF BEER - Bobková, Alica; Kunová, Simona; Bobko, Marek; Zeleňáková, Lucia; Lopašovsk½, Ľubomír; Melounová, Alexandra (Journal of microbiology, biotechnology and food sciences, 2013)
The aim of this article was the evaluation of physicochemical (pH value, ethanol content and initial worth extract) and sensory properties of beer samples. The basic sensory properties are: color, limpidity, foaming (foam stability), followed by smell and taste beer. Beer of pilsner type with various concentration of saccharose was produced. The range of pH values varied from 5.36 (sample no. 4) to 5.51 (sample no. 2). Sample no. 1 without saccharose had pH value 4.98. The initial wort extract for light beers from 11.00 to 12.99 % in samples no. 1 and 2. Sample with 50 % saccharose and sample no. 3 did not meet the requirements of legislation. The lowest content of ethanol was in sample no. 4 (4.2 %) with 50 % addition of saccharose. The highest content of ethanol was in sample no. 1 (5.12). Sensory properties were evaluated as bad in sample no. 4 in several parameters. Addition of saccharose has a negative impact on the sensory properties of beer.